Board and financial performance: A bibliometric and social network analysis research in Indonesia - Setyono, Primanita; Sutopo, Bambang (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study conducts a comprehensive bibliometric analysis examining the relationship between board and financial performance in Indonesia, analyzing 61 Scopus-indexed articles (2011-2025) using VOSviewer software. Employing dual methodology combining bibliometric and social network analysis, the research maps publication trends, key contributors, co-citation networks, and keyword co- occurrence patterns. Findings from Scopus database reveal substantial research growth with 76% of global publications emerging in the last eleven years, though Indonesian research represents only 9.6% globally. Key insights include: increased scholarly interest, research concentration in major Indonesian universities; dominance of corporate governance themes; and emerging interest in board diversity, Sharia governance, and environmental performance. This first comprehensive bibliometric study of board-financial performance literature in Indonesian context provides scholars, policymakers, and practitioners systematic understanding of research priorities, influential works, and collaborative networks, enabling strategic research planning and evidence-based governance policy development in emerging markets.